Fruit and vegetable intake, physical activity, and functional fitness among older adults in urban Alaska - Allexis Mahanna; Britteny M. Howell; Amber K. Worthington; Leslie C. Redmond; Vanessa Y. Hiratsuka (International Journal of Circumpolar Health)
Older adults often face barriers to obtaining recommended diet, physical activity, and fitness levels. Understanding these patterns can inform effective interventions targeting health beliefs and behavior. This cross-sectional study included a multicultural sample of 58 older adults (aged 55+ years, M=71.98) living in independent senior housing in urban Southcentral Alaska. Participants completed a questionnaire and the Senior Fitness Test that assessed self-reported fruit and vegetable intake, physical activity, self-efficacy, and functional fitness. T-tests and bivariate correlation analyses were used to test six hypotheses. Results indicated that participants had low physical activity but had a mean fruit and vegetable intake that was statistically significantly higher than the hypothesized “low” score. Only 4.26% of participants met functional fitness standards for balance/agility, and 8.51% met standards for lower-body strength. However, 51.1% met standards for upper-body strength and 46.8% met standards for endurance The results also indicated that nutrition self-efficacy and exercise self-efficacy were positively related to fruit and vegetable intake and physical activity levels, respectively. Interestingly, income was not related to nutrition or activity patterns. These data complicate the picture on dietary and physical activity patterns for older adults in Alaska and offer recommendations for future health promotion activities.